Love, Sex, Communism: A Discussion - Gleeson, Jules Joanne; Rosales, Jose; Culp, Andrew (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Jules Joanne Gleeson, Jose Rosales and Andrew Culp Title (English): Love, Sex, Communism: A Discussion Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 56-92 Page Count: 37 Citation (English): Jules Joanne Gleeson, Jose Rosales and Andrew Culp, “Love, Sex, Communism: A Discussion,” Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 56-92.